2017
DOI: 10.1371/journal.pone.0177482
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Great East Japan earthquake on microscopic polyangiitis: A retrospective observational study

Abstract: BackgroundAntineutrophil cytoplasmic antibody-associated vasculitis is triggered by environmental factors, including silica dust exposure. Repeated tsunami waves brought a large volume of silica-containing sludge inland after the Great East Japan earthquake in 2011. We aimed to determine if the serious disaster influenced the clinical features of the microscopic polyangiitis.MethodsThis is an observational retrospective study conducted in a single institute. A total of 43 patients were included based on the CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…An association between silica exposure and MPO-AAV has been consistently observed 24,25 . The high prevalence of silica in the natural environment (for example, in cement) is one proposed explanation for the apparent upsurge in AAV incidence following major earthquakes in 1995 and 2011 in Japan 26,27 . However, this correlation was not replicated in the aftermath of the 2011 earthquake in Christchurch, New Zealand 28 , a discordance that highlights the potential importance of AAV gene-environment interactions.…”
Section: Risk Factors and Disease Determinantsmentioning
confidence: 99%
“…An association between silica exposure and MPO-AAV has been consistently observed 24,25 . The high prevalence of silica in the natural environment (for example, in cement) is one proposed explanation for the apparent upsurge in AAV incidence following major earthquakes in 1995 and 2011 in Japan 26,27 . However, this correlation was not replicated in the aftermath of the 2011 earthquake in Christchurch, New Zealand 28 , a discordance that highlights the potential importance of AAV gene-environment interactions.…”
Section: Risk Factors and Disease Determinantsmentioning
confidence: 99%
“…These observations suggest that silica dust in the air, caused by the massive destruction and subsequent reconstruction of the cities 22 and by the marine sludge and sediments deposited in the subsequent tsunami disaster, 23 might have affected the presentation of AAV, especially its respiratory manifestations such as pulmonary haemorrhage and interstitial pneumonitis. However, in a contrasting study, no difference in the incidence of AAV was observed before versus after the February 2011 earthquake in Christchurch, New Zealand.…”
Section: [H2] Environmental Factorsmentioning
confidence: 99%
“…20 Although the association of silica with AAV has been intensely debated, a systematic review and meta-analysis confirmed the association between silica dust exposure and development of AAV. 21 Moreover, morbidity and disease severity increased substantially in patients with AAV after the great earthquakes in Japan (Hanshin-Awaji in 1995 22 and East Japan in 2011 23 ).…”
Section: [H2] Environmental Factorsmentioning
confidence: 99%
“…Takeuchi et al. showed evacuation of silica influenced by the development of ANCA-associated vasculitis after the Great East Japan earthquake 15 . Although the causes of vasculitis are largely unknown, CCR8-mediated allergic stimuli could be part of the pathogenesis in pauci-immune types of vasculitis.…”
Section: Discussionmentioning
confidence: 99%